2022
DOI: 10.3389/fpsyg.2022.887494
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ emotional exhaustion before and during the COVID-19 pandemic: Neither emotional exertion nor vacation feeling

Abstract: PurposeIn this paper, we use latent change models to examine the changes in in-service teachers’ emotional exhaustion before and during the COVID-19 pandemic. As a result of the pandemic, teachers are confronted with challenging tasks, which can lead to stress and burnout. Resultingly, teachers’ stress experiences have been examined in different studies. However, often the change in those experiences remains unclear. Against this background, we investigate longitudinally how the emotional exhaustion of a cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In contrast, Hilger et al (2021) reported a small but significant decrease in work-related fatigue between January and May 2020 and no change in teachers’ job satisfaction. Finally, using longitudinal data from 2016, 2019, and summer 2020 (assessed between July and October), Bleck and Lipowsky (2022) did not find an increase in veteran teachers’ emotional exhaustion from 2019 to 2020.…”
Section: Teachers’ Emotional Exhaustion and Enthusiasm During The Pan...mentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, Hilger et al (2021) reported a small but significant decrease in work-related fatigue between January and May 2020 and no change in teachers’ job satisfaction. Finally, using longitudinal data from 2016, 2019, and summer 2020 (assessed between July and October), Bleck and Lipowsky (2022) did not find an increase in veteran teachers’ emotional exhaustion from 2019 to 2020.…”
Section: Teachers’ Emotional Exhaustion and Enthusiasm During The Pan...mentioning
confidence: 70%
“…As an exception (with a baseline measure) and in contrast to our findings, Weißenfels et al (2022) found no significant increase in teachers’ emotional exhaustion at the onset of the pandemic: Their results indicated a significant increase in depersonalization and lack of accomplishment, but no increase in emotional exhaustion. Additionally, Bleck and Lipowsky (2022), also with a baseline measure, found no increase in emotional exhaustion among German teachers. One explanation for the different results between their study and ours might be that they investigated highly experienced teachers from nonacademic track schools during the first lockdown, whereas we surveyed mid-career teachers from both academic and nonacademic track schools in 2021 at the end of the second lockdown.…”
Section: Discussionmentioning
confidence: 83%
“…Research conducted in Germany provides a nuanced perspective. While Bleck and Lipowsky (2022) and Weißenfels et al (2022) found that teachers' emotional exhaustion remained stable during the initial months of the pandemic, Federkeil et al (2020) have reported an increase in teachers' emotional exhaustion.…”
Section: Teachers' Well-being During the Covid-19-pandemicmentioning
confidence: 99%
“…The potential decline in teachers' well-being during and following the pandemic is a significant concern, as it may have implications for their self-efficacy and commitment (Bardach et al, 2019), which in turn can affect students' learning outcomes. As also stated by Bleck and Lipowsky (2022), research efforts should prioritize examining this matter. In that sense, well-being interventions for teachers have been proposed, but empirical evidence of their effectiveness is still scarce (Dreer and Gouasé, 2022).…”
Section: Reflections For Researchmentioning
confidence: 99%
“…In this context, reports during the COVID-19 health crisis indicated that schoolteachers saw significant QoL decreases compared to before the pandemic, due to longer work hours and deteriorated work-family balance (8,10). Remote working among teachers was also reported as a factor associated with increased burnout, stress, and high emotional demands (11,12) together with reports of significant mental health deteriorations like higher levels of distress, worsened lifestyle quality, and increased emotional exhaustion (13)(14)(15). In this regard, pre-pandemic reports indicated high rates of musculoskeletal disorders (MSD) among schoolteachers linked with significant QoL particularly their mental QoL (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%